PEMANFAATAN PAKAN IKAN JUWI (ANADONTOSTOMA CHUCUNDA) OLEH KEONG MACAN (BABYLONIA SPIRATA L.) PADA MEDIA BUDIDAYA DENGAN SALINITAS BERBEDA - Diana Rachmawati; Istiyanto Samidjan; Titik Susilowati (Fakultas Perikanan Universitas Pekalongan, 2017)
This research aims to study the effect of cultivation media with the salinity differences on the feed usage, growth, osmotic work (TKO) and survival rate of Spotted Babylon (Babylonia spirata L.) and to find the best cultivation media with the salinity differences on the feed usage, growth, osmotic work (TKO) and survival rate of Spotted Babylon (B. spirata L.). The animals used in this study were obtained from Jepara water area with the average weight of 8,37±0,032 g/. There were 81 animals and raised in 56 days. The natural feed to give was Juwi fish with the amount of 5% of their body weight per day. The research method used in this study was a laboratory experiment with completely randomized design. The treatment use was the salinity differences of the cultivation media with salinity rate of A (27 ppt), B (31 ppt) and C (35 ppt). The results show that the salinity differences of the cultivation media significantly affected (P<0.01) on the feed usage, growth, osmotic performance, but insignificantly affected on the survival rate of Spotted Babylon (B. spirata L.) The cultivation media with the salinity rate of 31 ppt was the best salinity for the feed usage, growth, and osmotic performance of Spotted Babylon (B. spirata L.)Keywords: Spotted Babylon (Babylonia spirata L.), feed usage, salinity, domestication.